Pump‐Probe Fragmentation Action Spectroscopy: A Powerful Tool to Unravel Light‐Induced Processes in Molecular Photocatalysts. (1st March 2017) - Imanbaew, Dimitri; Lang, Johannes; Gelin, Maxim F.; Kaufhold, Simon; Pfeffer, Michael G.; Rau, Sven; Riehn, Christoph
Abstract: We present a proof of concept that ultrafast dynamics combined with photochemical stability information of molecular photocatalysts can be acquired by electrospray ionization mass spectrometry combined with time‐resolved femtosecond laser spectroscopy in an ion trap. This pump‐probe "fragmentation action spectroscopy" gives straightforward access to information that usually requires high purity compounds and great experimental efforts. Results of gas‐phase studies on the electronic dynamics of two supramolecular photocatalysts compare well to previous findings in solution and give further evidence for a directed electron transfer, a key process for photocatalytic hydrogen generation.